Meta‐analysis on continuous nerve monitoring in thyroidectomies. Issue 12 (3rd August 2021) - Ku, Dominic; Hui, Michelle; Cheung, Phylannie; Chow, Oliver; Smith, Mark; Riffat, Faruque; Sritharan, Niranjan; Kamani, Dipti; Randolph, Gregory
Abstract: In the last decade, the introduction of continuous intraoperative recurrent laryngeal nerve (RLN) monitoring (C‐IONM) has enabled the operator to verify the functional integrity of the vagus nerve–recurrent laryngeal nerve (VN‐RLN) axis in real‐time. We aim to present the current evidence on C‐IONM utility for thyroid surgery by conducting the first meta‐analysis on this technique. A systematic review of literature was conducted by two independent reviewers via Ovid in the Medline, EMBASE, and Cochrane reviews databases. The search was limited to human subject research in peer‐reviewed articles of all languages published between Jan 1946 and April 2020. Medical subject headings (MeSH) terms utilized were thyroid surgery, thyroidectomies, recurrent laryngeal nerve, vagal nerve, monitor, and stimulation. Thirty‐eight papers were identified from Ovid, another six papers were identified by hand‐search. A random effect meta‐analysis was performed with assessment of heterogeneity using the I 2 value. A total of 23 papers that investigated the use of continuous vagal nerve monitoring during thyroid surgery were identified. The proportion of nerves at risk (NAR) with temporary RLN paralysis postoperation was 2.26% (95% CI: 1.6–2.9, I 2  = 37). The proportion of NAR with permanent RLN palsy postoperation was 0.05% (95% CI: 0.08–0.2, I 2  = 0). In this meta‐analysis, there is one case of temporary vagal nerve paralysis secondary to VN electrode dislodgement, and a case of hemodynamic instability manifested in bradycardia and hypotension in the initial phase of surgery shortly after calibration. C‐IONM is a safe and effective means by which RLN paralyses in thyroid surgery can be reduced.